Familial trigeminal neuralgia – a systematic clinical study with a genomic screen of the neuronal electrogenisome - Di Stefano, Giulia (Cephalalgia, 2020)
OBJECTIVE: This cross-sectional study examined, for the first time, a large cohort of patients with trigeminal neuralgia, to ascertain the occurrence of familial cases, providing a systematic description of clinical features of familial disease. Since there is evidence linking hyperexcitability of trigeminal ganglion neurons to trigeminal neuralgia, we also carried out an exploratory genetic analysis of the neuronal electrogenisome in these patients. METHODS: We recorded familial occurrence by systematically interviewing all patients with a definite diagnosis of classical or idiopathic trigeminal neuralgia. We found 12 occurrences of trigeminal neuralgia with positive family history out of 88 enrolled patients. Whole-exome sequencing was carried out in 11 patients. We concentrated on the genetic variants within a 173-gene panel, comprising channel genes encoding sodium, potassium, calcium, chloride, transient receptor potential channels, and gap junction channels. Gene expression profiles were based on published RNA sequencing datasets of rodent/human trigeminal ganglia tissues, with a focus on genes related to neuronal excitability. RESULTS: In patients with familial trigeminal neuralgia, pain was more often located in the right, second division. All patients reported triggers. Four patients experienced concomitant continuous pain. Whole-exome sequencing analysis within the trigeminal ganglion electrogenisome identified 41 rare variants in ion channels, consisting of variants in sodium channels (6), potassium channels (10), chloride channels (5), calcium channels (7), transient receptor potential channels (12), and gap junction channels (1). In one patient, a previously profiled gain-of-function mutation in SCN10A (Nav1.8 p.Ala1304Thr), previously reported in painful neuropathy, was found; this variant was not present in unaffected siblings. CONCLUSIONS: Our results suggest that familial occurrence of trigeminal neuralgia is more common than previously considered. Although our results demonstrate variants in genes encoding voltage-gated ion channels and transient receptor potential channels within these patients, further study will be needed to determine their roles in the pathogenesis of trigeminal neuralgia.